2005
DOI: 10.1080/14786430500228663
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bulk melting of small metal clusters

Abstract: We present an analytical solution to the two-parabola Landau model, applied to melting of metal particles with sizes in the nanoscale range. The results provide an analytical understanding of the recently observed pseudo-crystalline phase of nanoscale Sn particles. Liquid skin formation as a precursor of melting is found to occur only for particles with radii, greater than an explicitly given critical radius. The size effect of the melting temperature and the latent heat has been calculated and quantitative ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
5
35
0
Order By: Relevance
“…More realistic assumptions are either the formation of a liquid or liquid-like layer at temperatures significantly below the melting temperature or a continuous process of melting starting at the surface. Thermodynamic calculations support these models [3435]. Sakai [34] concludes that the phenomenon of a liquid-like surface layer is, at least for the example of lead, restricted to particles larger than a critical size in the range of 4 nm; otherwise, the particles melt all at once.…”
Section: Reviewmentioning
confidence: 97%
“…More realistic assumptions are either the formation of a liquid or liquid-like layer at temperatures significantly below the melting temperature or a continuous process of melting starting at the surface. Thermodynamic calculations support these models [3435]. Sakai [34] concludes that the phenomenon of a liquid-like surface layer is, at least for the example of lead, restricted to particles larger than a critical size in the range of 4 nm; otherwise, the particles melt all at once.…”
Section: Reviewmentioning
confidence: 97%
“…29͒ and ZrO 2 . 30 Additionally, Chang and Johnson 31 show that for very small particles a perfect structure is thermodynamically impossible. Their study shows an increasing disorder from the center to the surface of particles.…”
Section: Discussionmentioning
confidence: 99%
“…The lower density of nanoparticles than in conventional material is in agreement with the literature, which indicated that in the case of nanoparticles, there is a reduction in the material density caused by high contribution of surface layers, which are less densely packed than the bulk. 33 The XRD analysis was conducted on GoHAP, commercial HAp (NanoXIM), and a plate from a pig's shank bone (Figure 2). The XRD results confirmed that the material is a pure well crystalline hexagonal HAp with nano-sized particles.…”
Section: Nanoparticles Characterizationmentioning
confidence: 99%